O desvio da regra ‘uma ação um voto’ induz restrição de crédito? - Granzotto, Alberto (2020)
Recent studies have sought to explain how financing constraints through controlling shareholder moral hazard. Thus, a difficulty in accessing credit due to the dissimilarity between internal and external capital may be due to the majority-owned private conduct by its higher control. Based on this premise, the present study seeks to analyze the impact of controlling shereholder’s moral hazard in cash flow sensitivity of cash of restricted and unrestricted credit Brazilian firms listed in Brasil, Bolsa e Balcão (B3) between 1996 and 2017. To achieve the strategic objective, regressions were applied through Minimum Ordinary Squares estimated by robust random effects. First, we seek to measure the moral hazard of controlling shareholder according the wedge of control, that is, an escape from the "one share voting" rule. Subsequently, the wedge of control is used as a financial constraint proxy, in which companies with larger share deviations (smaller share deviations) represented the companies with greater (smaller) financial constraints. The purpose of this subdivision is to compare the cash flow sensitivity of cash (financial decision from the perspective of the financial constraint) of restricted firms (largest deviations) and credit restrictions (minor deviations). A general way was evidenced as a distinct behavior between credit restricting companies (smaller share deviations) compared to restricted companies (larger share deviations), i.e., the moral hazard of controlling shareholder affected differently by subgroups, substantially by cash flow sensitivity of cash. Specifically, as unrestricted firms (lower triggered deviations) it was evidenced that cash flow does not statistically affect cash variation (either at time t or at time t -1). Alternatively, as firms restrict credit (larger deviations), considering a positive and non-zero coefficient to no cash flow, that is, the resources in the internal resources of Brazilian firms have a positive impact and the cash policy of firms that secured) of access to credit (both at time and at time t -1). Because differences displayed may be justified by the fact that a voting rule aggravates agency conflicts between controlling shareholder and credit sources (minority shareholders and creditors), send a negative signal to outside investors that their assets may be expropriated. Thus, the results are consistent with the argument that the moral hazard of controlling shareholder induces financing constraints. Finally, a major contribution of the present study concerns a proposed wedge of controlas a proxy for financial constraint, because it reflects substantially the moral hazard of controlling shareholder, as well as weak legal protection for minority shareholders due to their incipience in the financial and corporate governance markets, in which they are conditioning and aggravatin of financial constraintss. Therefore, the use of wedge of control as a financial constraint measure allows the identification of a Brazilian financial market, as well as the reflection of a specific way as possible financial constraints present in Brazil.